2008
DOI: 10.1002/uog.5422
|View full text |Cite
|
Sign up to set email alerts
|

OC014: Left atrial dynamics in fetuses of diabetic mothers

Abstract: Objectives: Abnormal uterine bleeding needs careful evaluation to exclude uterine pathology, particularly endometrial cancer. The combination of Saline Infusion Sonography (SIS) and endometrial aspiration is a reliable tool for this purpose. The objective of this study was to evaluate the effect of SIS on the quality of the endometrial aspiration specimen in women with abnormal uterine bleeding by performing both examinations in one session. Methods: In this single-blind randomised controlled trial, 113 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…However, large cardiology centres usually have well-structured programmes of fetal cardiology with advanced techniques for the diagnosis and even treatment of some CHD in utero. Interesting clinical research has been performed on several cardiac fetal topics, including screening of CHD in selected pregnant women, abnormalities of the septum primum, cardiovascular abnormalities in fetuses of diabetic mothers, diastolic dysfunction, restriction of flow across the foramen ovale, treatment of fetal arrythmias and fetal interventions for aortic stenosis and hypoplastic left heart syndrome 545100101102103104105106107108109110111112113…”
Section: Outcomes After Medical Surgical or Interventional Treatmentmentioning
confidence: 99%
“…However, large cardiology centres usually have well-structured programmes of fetal cardiology with advanced techniques for the diagnosis and even treatment of some CHD in utero. Interesting clinical research has been performed on several cardiac fetal topics, including screening of CHD in selected pregnant women, abnormalities of the septum primum, cardiovascular abnormalities in fetuses of diabetic mothers, diastolic dysfunction, restriction of flow across the foramen ovale, treatment of fetal arrythmias and fetal interventions for aortic stenosis and hypoplastic left heart syndrome 545100101102103104105106107108109110111112113…”
Section: Outcomes After Medical Surgical or Interventional Treatmentmentioning
confidence: 99%
“…Zielinsky et al . () and Miyague et al . () have already studied the influence of fetal breathing on the mobility of the septum primum and atrioventricular valve flows.…”
Section: Discussionmentioning
confidence: 85%
“…This can be demonstrated by the analysis of mitral and tricuspid valve flows, which shows an E/A ratio < 1 throughout gestation, with increasing values towards term (Harada et al , ). Left atrial shortening fraction has been shown to be lower in fetuses of diabetic mothers than in normoglicemic mothers as a result of myocardial hypertrophy (Zielinsky et al , ). In the normal fetus, however, the physiological behavior of the left atrial shortening fraction has not been fully studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Several parameters and Doppler indexes have been used to assess diastolic function 7 in order to improve diagnosis, obtain a clear prognosis, and follow up the effect of therapeutic interventions. Alternative methods to transmitral flow Doppler have been studied to assess fetal diastolic function 7,9,11,[18][19][20] because the peculiar characteristics of fetal circulation have rendered traditional methods insufficient.…”
Section: Discussionmentioning
confidence: 99%